1994
DOI: 10.1007/bf00417694
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen: its mode of formation and contribution to hepatic glucose output in postabsorptive humans

Abstract: SummaryTo assess the relative contributions of gluconeogenesis and glycogenolysis to overall hepatic glucose output in postabsorptive normal humans and those of the indirect and direct pathways for glycogen synthesis, we studied six normal volunteers, who had been fasted for 16 h to reduce their hepatic glycogen stores, and then ingested glucose (250 g over 10 h) enriched with [6-3H] glucose to replenish and label their hepatic glycogen. After a 10-h overnight fast, release of the [6-3H] glucose into the circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Previous estimates of indirect pathway glycogen formation in humans have ranged from 23 to 60% (34, 35, 46-48, 50, 54, 58). Our data are compatible with those of Pimenta et al (47), Peterson et al (46), and Magnusson et al (34,35), who found the indirect pathway to account for 33, 37, 23, and 35%, respectively, of overall glycogen formation.…”
Section: Discussionsupporting
confidence: 83%
“…Previous estimates of indirect pathway glycogen formation in humans have ranged from 23 to 60% (34, 35, 46-48, 50, 54, 58). Our data are compatible with those of Pimenta et al (47), Peterson et al (46), and Magnusson et al (34,35), who found the indirect pathway to account for 33, 37, 23, and 35%, respectively, of overall glycogen formation.…”
Section: Discussionsupporting
confidence: 83%
“…Determinations of the contribution of gluconeogenesis to glucose production in healthy subjects after an overnight fast have ranged from 25 to 70% (19,(33)(34)(35)(36)(37)(38)(39)(40)(41). That spread may be attributed in part to dietary preparation, but even with the same preparation, there has been marked variation in glycogen stores at the beginning of fasting (34).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Rothman et al (27), Petersen et al (28), and Magnusson et al (29) have quantified gluconeogenesis indirectly by subtracting the rate of hepatic glycogenolysis, measured by magnetic resonance imaging, from the tracer isotopemeasured rate of glucose production. Other methods have used glycogen-labeling technique (30) and mass isotopomer distribution analysis using [U-13 C]glucose tracer (31). All of these methods have resulted in estimates of gluconeogenesis in normal healthy subjects during the postabsorptive state to be in the range of 25 to 60%.…”
Section: Discussionmentioning
confidence: 99%